Religious Koplo Dangdut Music: Cultural Identity and Religious Expression - Arif Al Wasim; Handoyo; Nurma Khusna Khanifa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
Humans and culture are two things that are interrelated and cannot be separated from eachother. Religion and music are two things that have a relationship with culture. Religiousmessages and da'wah are often displayed in the packaging of musical art and bring religiousmusic. The development of music in Indonesia in the past two decades gave rise to one ofthe dangdut music sub-genres, known as Koplo dangdut, which in its performance also ofteninserted religious messages and presented them in the religious Koplo dangdut format. Thisarticle examines Koplo dangdut as the cultural identity and religious expression of coastalcommunities, which is seen as a cultural reality, with an anthropological approach. The studyis conducted with an ethical perspective, where the writer only observes without beingdirectly involved in the object of observation. The main data in this study is the religiouskoplo dangdut music video from YouTube. Koplo dangdut, which is famous for its vulgarityand directness in the lyrics of the song, reflects the cultural conditions of the song performerswith a background in coastal Javanese society. However, the religious side of the Koplo dangdutmusic genre still appears in the religious koplo dangdut sub-genre. Religious expressions thatappear in the stage of religious koplo dangdut are artistic expressions which include dimensionsof belief (ideology), experience (ahlak), and knowledge.